Design, synthesis, and evaluation of 4-(3-(3,5-dimethylisoxazol-4-yl)benzyl)phthalazin-1(2H)-one derivatives: potent BRD4 inhibitors with anti-breast cancer activity - Li, Yingpeng; Chu, Xinhong; Yin, Yu; Li, Hongkun; Fu, Hui; Feng, Xinchi; Deng, Yanru; Ge, Jun (Frontiers in Pharmacology, 2023)
BRD4 inhibitors have demonstrated promising potential in cancer therapy. However, their therapeutic efficacy in breast cancer varies depending on the breast cancer subtype, particularly in the treatment of TNBC. In this study, we designed and synthesized 94 derivatives of 4-(3-(3,5dimethylisoxazol-4-yl)benzoyl)phthalazin-1(2H)-one to evaluate their inhibitory activities against BRD4. Notably, compound DDT26 exhibited the most potent inhibitory effect on BRD4, with an IC50 value of 0.237 ± 0.093 μM. DDT26 demonstrated significant anti-proliferative activity against both TNBC cell lines and MCF-7 cells. Intriguingly, the phthalazinone moiety of DDT26 mimicked the PAPR1 substrate, resulting in DDT26 displaying a moderate inhibitory effect on PARP1 with an IC50 value of 4.289 ± 1.807 μM. Further, DDT26 was shown to modulate the expression of c-MYC and γ-H2AX, induce DNA damage, inhibit cell migration and colony formation, and arrest the cell cycle at the G1 phase in MCF-7 cells. Our findings present potential lead compounds for the development of potent anti-breast cancer agents targeting BRD4.